Prosocial lie-telling in preschoolers: The impacts of ethnic background, parental factors, and perceived consequence for the partner - Dobrin-De Grace, Roksana; Ma, Lili (Frontiers in Psychology, 2023)
This study explored prosocial lie-telling behavior in 4- to 5-year-old children from two ethnic groups: European Canadian (n = 49; excluding Eastern European Canadian) and Chinese Canadian (n = 45). Children completed an online experiment involving two real-life politeness situations. In the first situation, children were asked whether they thought someone with a red mark on their face looked okay for a photo or a Zoom party (Reverse Rouge Task). In the second situation, upon hearing the researcher’s misconception about two pieces of artwork, children were asked whether they agreed with the researcher (Art Rating Task). Parents completed questionnaires that measured their levels of collectivist orientation and parenting styles. Contrary to our hypotheses, the likelihood of children telling a prosocial lie did not vary as a function of their ethnic group or the presence of a perceived consequence for the partner, nor was it predicated by parental collectivist orientation. Interestingly, prosocial liars were more likely to have authoritative parents, whereas blunt-truth tellers were more likely to have permissive parents. These findings have important implications for the ways in which certain parenting styles influence the socialization of positive politeness in children. In addition, the similar rates of prosocial lying across the two ethnic groups suggest that children who are born and raised in Canada may be much more alike than different in their prosocial lie-telling behavior, despite coming from different ethnic backgrounds.